The Link Between a Husband’s Trust in Informal Institutions and Domestic Violence Against His Wife: Evidence From Pakistan - Akter, Sonia (Journal of interpersonal violence, 2022)
The global and national push to strengthen informal institutions? role in increasing rural households? access to justice has often met with skepticism in South Asia. This is because the impact of such initiatives on women?s welfare is debatable in many contexts due to reports of informal institutions? hostile and oppressive behavior toward women. This study contributes to this debate by presenting the first empirical evidence of gender difference in trust in informal village institutions. The study also tests the relationship between a husband?s trust in informal institutions and his tendency to commit physical violence against his wife. It uses the Pakistan Rural Household Panel Survey datasets of more than 2,000 households from three provinces (Punjab, Sindh, and Khyber Pakhtunkhwa) of Pakistan. Trust in local political institutions is measured by (a) respondent?s reliance on village institutions for handling general community affairs and maintaining law and order and (b) respondent?s perceptions of local government?s effectiveness in dispute settlement and ensuring public security. Men?s and women?s trust in informal village institutions and their perceptions of these institutions? legitimacy do not significantly differ in most cases. Women exhibit a greater trust and confidence in informal institutions that hold regular resident meetings than in those that do not. The results also reveal a significant negative relationship between a husband?s trust in informal institutions and the incidence of physical violence against his wife. Greater trust in informal institutions has a significant positive correlation with a husband?s psychological well-being, his relationship with family, and his perceptions of institutional legitimacy. The findings imply that well-performing informal institutions work as an indirect deterrent for domestic violence in the study areas of Pakistan.